1993
DOI: 10.1104/pp.103.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Gene from Camptotheca acuminata Is Differentially Regulated by Wounding and Methyl Jasmonate

Abstract: We have isolated a gene, hmgl, for 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMCR) from Camptotheca acuminata, aChinese tree that produces the anti-cancer monoterpenoid indole alkaloid camptothecin (CPT). HMCR supplies mevalonate for the synthesis of the terpenoid component of CPT as well as for the formation of many other primary and secondary metabolites. In Camptotheca, hmgl transcripts were detected only in young seedlings and not in vegetative organs of older plants. Regulation of the hmgl promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…We showed that the Arabidopsis HMGP gene promoter is not induced in wounded leaves of transgenic tobacco plants containing construct (-857/+64)HMGP-GUS. Under similar experimental conditions, the promoter of the C. acuminata hmgl gene was highly induced in transgenic tobacco plants (Burnett et al, 1993). Our results suggest that the Arabidopsis HMGP gene is not involved in the synthesis of specific isoprenoids in response to wounding.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We showed that the Arabidopsis HMGP gene promoter is not induced in wounded leaves of transgenic tobacco plants containing construct (-857/+64)HMGP-GUS. Under similar experimental conditions, the promoter of the C. acuminata hmgl gene was highly induced in transgenic tobacco plants (Burnett et al, 1993). Our results suggest that the Arabidopsis HMGP gene is not involved in the synthesis of specific isoprenoids in response to wounding.…”
Section: Discussionsupporting
confidence: 49%
“…Specific potato HMGR genes are differentially expressed in response to wounding and pathogen challenge (Yang et al, 1991;Choi et al, 1992). lnduction of the Camptotheca acuminata hmgl gene by wounding has been reported in transgenic tobacco plants (Burnett et al, 1993). Arabidopsis contains two differentially expressed HMGR genes, HMGl and HMGP.…”
Section: Introductionmentioning
confidence: 99%
“…Severa1 feedback regulatory mechanisms control transcription of the reductase gene, and its catalytic activity is modulated by both covalent modification and noncovalent interactions (Goldstein and Brown, 1990). In contrast, plants, which produce much more diverse products from the mevalonate pathway in various tissues and organelles, contain multiple, differentially regulated genes for HMG-COA reductase (Narita and Gruissem, 1989;Yang et al, 1991;Choi et al, 1992;Chye et al, 1992;Genschik et al, 1992;Burnett et al, 1993;Enjuto et al, 1994). Different reductase genes are expressed in different parts of the plant (Chye et al, 1992;Genschik et al, 1992;Enjuto et al, 1994), at different stages of development (Narita and Gruissem, 1989), and in response to various stresses (Yang et al, 1991;Choi et al, 1992;Genschik et al, 1992).…”
Section: Molecular Biologymentioning
confidence: 99%
“…It was shown that wounding of plant tissues induced hmg1 gene that encodes HMGR enzymes involved in the biosynthesis of phytosterols and its induction was suppressed by elicitors in a potato 24) and methyl jasmonate in Camptotheca acuminata. 25) These findings might explain the decrease in the content of b-sitosterol in the tissues treated with MeJA. In our previous communication, the involvement of 1-deoxy-D-xylulose 5-phosphate (DOXP) pathway, so called mevalonate-independent pathway, in the biosynthesis of SDB and phytol was suggested, while b-sitosterol was indicated to be biosynthesized via the mevalonate pathway.…”
mentioning
confidence: 90%